Interest rate rules, rigidities and inflation risks in a macro-finance model - Roman Horváth; Lorant Kaszab; Ales Mars (Magyar Nemzeti Bank, 2021)
Long-term bond yields contain a risk-premium, an important part of which is compensation for inflation risks. The substantial increase in the Fed funds rate in the mid-2000s did not raise long-term US Treasury yields due to the reduction in the term premium (so-called Greenspan conundrum) which was typically thought to be exogenous for monetary policy. We show using a New Keynesian macro-finance model that the term premium is endogenous and is greatly influenced by the specification of the Taylor rule. Finally, we extend the model with frictions (richer fiscal setup and wage rigidity) that are known to help jointly match macro and finance data and estimate the model on US data in 1961-2007 by the generalized methods of moments and simulated methods of moments.
Keywords: E13; E31; E43; E44; 330; zero-coupon bond; nominal term premium; inflation risk; Taylor rule; New Keynesian; labor income taxation; wage rigidity; GMM; SMM